2009
DOI: 10.1007/978-3-642-04447-2_52
|View full text |Cite
|
Sign up to set email alerts
|

Some Experiments in Question Answering with a Disambiguated Document Collection

Abstract: Abstract. This paper describes our approach to the Question Answering -Word Sense Disambiguation task. This task consists in carrying out Question Answering over a disambiguated document collection. In our approach, disambiguated documents are used to improve the accuracy of the retrieval phase. In order to do this, we added a WordNet-expanded index to the document collection. The expanded index contains synonyms, hypernyms and holonyms of the words already in the documents. Question words are searched for in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The Robust-WSD task introduced in CLEF 2009 represents an interesting attempt to foster further investigation in this field. In 2008, we participated in the QA-WSD task using an index expansion method based on WordNet hypernyms, synonyms and holonyms, which exploited the disambiguated collection [1]. The results did not show any relevant difference between the use of disambiguation or not, although we observed that passages returned using the disambiguated collection and our method tended to be shorter with respect to the base system.…”
Section: Introductionmentioning
confidence: 90%
“…The Robust-WSD task introduced in CLEF 2009 represents an interesting attempt to foster further investigation in this field. In 2008, we participated in the QA-WSD task using an index expansion method based on WordNet hypernyms, synonyms and holonyms, which exploited the disambiguated collection [1]. The results did not show any relevant difference between the use of disambiguation or not, although we observed that passages returned using the disambiguated collection and our method tended to be shorter with respect to the base system.…”
Section: Introductionmentioning
confidence: 90%